A REALIZATION ON THE TEXTUAL MEANING OF THE INDONESIAN AND ENGLISH TRANSLATION OF 1 JOHN 3:1-24 - Irene Adryani Nababan (Jurnal Scientia, 2023)
This research entitled ‘A Realization on the Textual Meaning of the Indonesian and English Translation of 1 John 3:1-24’ has one objective. The data of this research is 1 John 3:1-2 taken from Alkitab TB LAI-Lite Application for Indonesian Translation and from the Gideon Bible-The Gideons International-English Standard Version for English Translation. The objective is to identify the realization on Theme and Rheme of the 1 John 3:1-24 in Indonesian and English Translation. The research methodology is qualitative research. The data of this research was analyzed by using some steps, they are segmenting the sentences into clauses, identifying the theme and rheme for each clause, determining the type of theme and rheme for each clause, and drawing conclusion. After analyzing the data of 1 John 3:1-24 taken from the Alkitab TB LAI-Lite Application for Indonesian Translation, it can be seen that there are 46 clauses and 1 sentences. As a result, the researcher concludes that from 46 clauses and 11 sentences, there are 46 clauses consist of topical theme and 11 sentences are consist of topical theme. Then, 31 clauses and 6 sentences consist of textual theme. And 1 clause and 3 sentences consist of interpersonal theme. After analyzing the data of 1 John 3: 1-24 taken from the Gideon Bible-The Gideons International-English Standard Version for English Translation, it can be seen that there are 49 clauses and 9 sentences in English Standard Version. As a result, the researcher concludes that from 49 clauses and 9 sentences, there are 49 clauses consist of topical theme and 8 sentences are consist of topical theme. Then, 26 clauses and 4 sentences consist of textual theme. And 3 clause and 3 sentences consist of interpersonal theme. The findings show that the three types of theme proposed by Halliday (1994) are realized in both translations. Those themes are Topical theme Interpersonal theme and Textual theme. The dominant themes in the texts is topical theme.